If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 8n + -9 Reorder the terms: 1 = -9 + 8n Solving 1 = -9 + 8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-8n' to each side of the equation. 1 + -8n = -9 + 8n + -8n Combine like terms: 8n + -8n = 0 1 + -8n = -9 + 0 1 + -8n = -9 Add '-1' to each side of the equation. 1 + -1 + -8n = -9 + -1 Combine like terms: 1 + -1 = 0 0 + -8n = -9 + -1 -8n = -9 + -1 Combine like terms: -9 + -1 = -10 -8n = -10 Divide each side by '-8'. n = 1.25 Simplifying n = 1.25
| 5(4m+1)=20 | | 2x+7-8x=13-15x+9x-6 | | x+0.09x=721 | | 279+0.38= | | 0=3(2x-8) | | 279=64-w | | 7-x=4-9x | | 6x+2x=1-x+7x-13 | | X-4.2=0.7x-4.8 | | 8038.4=6.28r^2+401.92 | | 2cos^2x+2sin^2x=2 | | 3x(x+1)(x+2)=30 | | 6d-3=8 | | -4(x-3)+5(x-1)=-18 | | x(x+1)(x+2)=30 | | 64=3v+13 | | 100+0.2x=150+0.15x | | -1-3x=-1+2-5x+x | | A=x+xyz | | 6x+13-5x=0 | | 2x+12=2x+61 | | 25=n-16 | | 4=9w-3 | | -6x+3(x-2)= | | -12-v=-2+v | | (2x-7)=(x+2) | | 0-9=33x | | 12x-9=9x+15 | | 7(5+7x)=-161 | | c^2-20x+100=0 | | 52=3+7p | | 5(x-1)+7=x+190 |